Rescue Strategy Concept for a Company in a Weakening Market - Nurfalah, Mohamad Hamzah; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2012)
PT ABC is a company located in Puncak Region West Java. Its main business is providing outdoor training activity, or known as outbound. To support its business, it is also facilitated with accommodation facility. Since the beginning of its business, a proper management principle is not being used properly by this company, therefore there’s an indication that this company will go to a bankruptcy. This paper is going to discuss about the alternatives to rescue this company from bankruptcy. Using the Altman’s z score prediction model, this paper will try to find out the real condition of this company toward bankruptcy. After that four alternatives of rescue strategy will be analyzed. These strategies are the strategies that hopefully will rescue this company from bankruptcy. The alternatives are refinancing, diversification of business, reorientation of business, or sell the company. Capital budgeting techniques, like NPV, IRR, PBP, etc will be used to analyze it. After that, decision tree will be used to pick the most promising alternative. Keywords: Bankruptcy, Capital Budgeting, NPV, Decision tree, Altman Z Score